Regeneration and reuse of microbial extracellular polymers immobilised on a bed column for heavy metal recovery. (15th March 2020) - Ajao, Victor; Nam, Kang; Chatzopoulos, Paraschos; Spruijt, Evan; Bruning, Harry; Rijnaarts, Huub; Temmink, Hardy
Abstract: Microbial extracellular polymeric substances (EPS) have gained increasing attention for various water treatment applications. In this study, EPS produced from nitrogen-limited glycerol/ethanol-rich wastewater were used to recover Cu 2+ and Pb 2+ from aqueous solutions. Continuous flow-through tests were conducted on a column packed with silica gel coated with polyethyleneimine, to which EPS were irreversibly attached as shown by optical reflectometry. These immobilised EPS excellently adsorbed Cu 2+ and Pb 2+, with 99.9% of influent metal adsorbed before the breakthrough points. Metal desorption was achieved with 0.1M HCl, with an average recovery of 86% for Cu 2+ and 90% recovery for Pb 2+ . For the first time, we successfully showed the possibility to regenerate and reuse the immobilised EPS for five adsorption-desorption cycles (using Cu 2+ as an example) with no reduction in the adsorbed amount at the breakthrough point ( q bp ). Based on the mass balance of the associated metal ions participating in the adsorption process, ion exchange was identified as the major mechanism responsible for Cu 2+ and Pb 2+ adsorption by EPS. The results demonstrate the potential of wastewater-produced EPS as an attractive and perhaps, cost-effective biosorbent for heavy metal removal (to trace effluent concentrations) and recovery (86–99%). Graphical abstract: Image 1 Highlights: EPS was immobilised on a column for continuous heavy metal adsorption and recovery. EPS could be regenerated and reused for repetitive adsorption-desorption cycles. 99.9% of Cu 2+ and Pb 2+ were adsorbed before the breakthrough point. 86–99% of adsorbed metal ions could be recovered. Ion-exchange was the major adsorption mechanism.